PELATIHAN SUMBER PEMBIAYAAN USAHA DALAM PENGEMBANGAN USAHA PADA UKM - Rasyid, Rosmita; Rahadani, Fansisca Puspita; Anggela, Nicole (Transpublika Publisher, 2023)
Collecting funding sources has always been a challenge for entrepreneurs. Nowadays, entrepreneurs feel that it's increasingly difficult to obtain the necessary capital to start and expand their businesses. Small and Medium Enterprises (UKM) often face various issues when searching for new funding sources. Various financing patterns for UKM have been devised to address the funding gap problem, especially the capital constraints that can hinder their innovative activities. The selected partner for the Community Service Program (PKM) is a handmade craft business called